Field School For Cacao Farmers in Bulili Village as An Effort to Improve Cacao Productivity in Sigi Regency, Central Sulawesi - Nabilla, Risya Mutiara; Sumiahadi, Ade (Research and Social Study Institute, 2025)
Background: Limited knowledge and skills among farmers are one of the main factors contributing to suboptimal cocoa productivity in Bulili Village, Nokilalaki District, Sigi Regency. Inadequate understanding of proper cocoa cultivation techniques and weak farm financial management practices hinder farmers’ ability to optimize production and income. Therefore, targeted capacity-building efforts are required to address these constraints and improve the sustainability of cocoa farming systems in the area.Aims: This community service activity aimed to enhance the knowledge and practical skills of cocoa farmers in Bulili Village regarding good cocoa cultivation practices and farm financial management. Ultimately, the program sought to increase cocoa productivity and improve farmers’ income.Method: The activity was conducted in Bulili Village, Nokilalaki District, Sigi Regency, from September to December 2023. The program was implemented in the form of a cocoa farmer field school. The stages of the activity included an initial survey through observations and interviews to identify farmers’ needs and problems, followed by five field school sessions (Field School 1–5) with materials tailored to the issues identified during the initial survey. An evaluation phase was conducted at the end of the program to assess participant satisfaction and the effectiveness of the activities.Results: The field school program was implemented successfully and ran smoothly throughout the activity period. The program received a very positive response from participants, as indicated by high levels of enthusiasm and active participation during all field school sessions. Participants also demonstrated a cooperative attitude in supporting the implementation of the activities until completion. Based on the evaluation results, farmers expressed satisfaction with the program and hoped that similar activities would continue in the future to help address agricultural challenges faced by cocoa farmers.